MENGIDENTIFIKASI KESIAPAN GURU SEKOLAH DASAR DALAM MENERAPKAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Dinda Fajar Chairani; Nurul Agustina Ginting; Oktaviani; Jaya Adi Putra; Mutia Yulita Sari (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a project that aims to strengthen character education by forming students who uphold the values ​​of Pancasila. In its application to the Merdeka Curriculum, especially in formal education environments, teachers play an important role as implementers who are trusted by the community. Educators educate students based on the curriculum and learning plans that have been designed. Therefore, teacher readiness in running this program is very crucial, because teachers are the key to the success of the implementation of the curriculum. The purpose of this study is to Identify the Readiness of Elementary School Teachers in Implementing the Pancasila Student Profile at SDN 188 Pekanbaru. This study uses a qualitative method. The observation instruments are interviews and documentation of teachers who have implemented the Pancasila Student Profile. According to the results of the study, teachers have begun to understand and can implement the Pancasila Student Profile Strengthening project. However, they still face several challenges such as lack of training, difficulties in forming student character, and limited communication and support from parents.